Faktor Lingkungan yang Berhubungan dengan Kejadian Filariasis Di Kabupaten Kuningan - Annashr, Nissa Noor; Amalia, Icca Stella (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Filariasis is an infectious disease caused by worms, which can attack the lymphatic system, resulting in abnormal enlargement of body parts, pain, severe disability, and social stigma. The spread of filariasis was influenced by various factors, one of them was environmental factors. Kuningan is one of the districts that become filariasis endemic areas in West Java. The purpose of the study was to analyze the relationship of environmental factors with filariasis cases. This study included analytic observational research using a case-control study design. The comparison of cases and controls was 1: 2. The population was all filariasis cases in Kuningan District, which amounted to 16 cases. The sampling technique used total sampling so that the sample size was 16 for the case group. The sampling technique for the control group used purposive sampling. The sample size for the control group was 32. The data on environmental factors and filariasis was taken by observation and interview. Data were analyzed by univariate, bivariate, and multivariate analysis. The bivariate analysis used a chi-square and fisher exact test, then multivariate analysis used multiple logistic regression. Bivariate analysis showed that from 12 independent variables, there were 3 variables that had a significant relationship with filariasis. Variable of wastewater disposal system, the presence of wire netting, ceiling construction had significant relationship with filariasis (p1 = 0.041 OR = 3.667 ; p2 = 0.03 OR = 5.44 and p3 = 0.033 OR = 3,857). This study proved that the wastewater disposal system was a dominant factor affecting filariasis.